Twenty-first-century popular fiction - Murphy, Bernice M. 1977-; Matterson, Stephen (Edinburgh University Press, 2018)
Provides a unique snapshot of themes and trends within popular fiction in the twenty-first centuryThis groundbreaking collection captures the state of popular fiction in present day. It features twenty new essays on key authors associated with a wide range of genres and sub-genres, providing chapter-length discussions of major post-2000 works of contemporary popular fiction. The lively, accessible and academically rigorous essays presented here cover a wider range of established popular fiction genres such as fantasy, horror and the romance, as well as more niche areas such as Domestic Noir, Steampunk, the New Weird, Nordic Noir and Zombie Lit. The collection will primarily appeal to undergraduate and postgraduate students but general readers may also find the focus on many of today's most prominent and influential authors to be of interest.Key FeaturesProvides students with a timely and accessible overview of current trends within contemporary popular fictionIncludes timely reassessments of recent fiction by established figures such as Stephen King, George R.R. Martin, Larry McMurtry, Neil Gaiman, J.K. Rowling, Jodi Picoult, China Miéville, Grant Morrison, Terry Pratchett and Nora Roberts as well as consideration of authors who have emerged more recently, amongst them Stephenie Meyer, Gillian Flynn, E.L. James, Hugh Howey, Cherie Priest, and Max BrooksIncludes supplementary material such recommended further reading at the end of each chapter.
Keywords: Geschichte 2000-2017; Literary Studies; LITERARY CRITICISM / General; American literature -- 21st century -- History and criticism; English fiction -- 21st century -- History and criticism; Popular literature -- 21st century -- History and criticism; Englisch; Unterhaltungsliteratur; Aufsatzsammlung